Detecting genotyping error using measures of degree of hardy-weinberg disequilibrium - John Attia (2018)
Tests for Hardy-Weinberg equilibrium (HWE) have been used to detect genotyping error, but those tests have low power unless the sample size is very large. We assessed the performance of measures of departure from HWE as an alternative way of screening for genotyping error. Three measures of the degree of disequilibrium (α, ,D, and F) were tested for their ability to detect genotyping error of 5% or more using simulations and a real dataset of 184 children with leukemia genotyped at 28 single nucleotide polymorphisms. The simulations indicate that all three disequilibrium coefficients can usefully detect genotyping error as judged by the area under the Receiver Operator Characteristic (ROC) curve. Their discriminative ability increases as the error rate increases, and is greater if the genotyping error is in the direction of the minor allele. Optimal thresholds for detecting genotyping error vary for different allele frequencies and patterns of genotyping error but allele frequency-specific thresholds can be nominated. Applying these thresholds would have picked up about 90% of genotyping errors in our actual dataset. Measures of departure from HWE may be useful for detecting genotyping error, but this needs to be confirmed in other real datasets. © 2010 The Berkeley Electronic Press. All rights reserved.